Brachial artery diameter as a marker for cardiovascular risk assessment: FMD-J study. (January 2018) - Maruhashi, Tatsuya; Soga, Junko; Fujimura, Noritaka; Idei, Naomi; Mikami, Shinsuke; Iwamoto, Yumiko; Iwamoto, Akimichi; Kajikawa, Masato; Matsumoto, Takeshi; Oda, Nozomu; Kishimoto, Shinji; Matsui, Shogo; et al.
Abstract: Background and aims: Baseline brachial artery (BBA) diameter has been reported to be a potential confounding factor of flow-mediated vasodilation (FMD). The purpose of this study was to evaluate the relationships between BBA diameter and cardiovascular risk factors and compare the diagnostic accuracy of BBA diameter in subjects without cardiovascular risk factors and patients with cardiovascular disease (CVD) with that of FMD. Methods: We measured BBA diameter and FMD in 5695 male subjects. In addition, we retrospectively investigated the incidence of cardiovascular events using another population sample consisting of 440 male subjects, to compare the accuracy of BBA diameter with that of FMD in predicting cardiovascular events. Results: BBA diameter and FMD significantly correlated with age, body mass index, systolic blood pressure, diastolic blood pressure, triglycerides, high-density lipoprotein cholesterol, and glucose as well as Framingham risk score. The prevalence of cardiovascular risk factors and CVD increased with the increase in BBA diameter and FMD. Area under the curve (AUC) value of the receiver operating characteristic (ROC) curve for BBA diameter to diagnose subjects without cardiovascular risk factors (0.59 vs. 0.62, p  = 0.001) or patients with CVD (0.58 vs. 0.64, p  < 0.001) was significantly lower than that for FMD. In the retrospective study, the AUC value of the ROC curve for BBA diameter to predict first major cardiovascular events was significantly lower than that of FMD (0.50 vs. 0.62, p  = 0.03). Conclusions: In men, BBA diameter was inferior to FMD for assessment of cardiovascular risk. Highlights: Baseline brachial artery (BBA) diameter was associated with cardiovascular (CV) risk. Flow-mediated vasodilation (FMD) was also associated with CV risk. In men, diagnostic accuracy of BBA diameter for CV risk was inferior to that of FMD. BBA diameter was inferior to FMD as a predictor of future cardiovascular events.